Effects of Parenteral Nutritional Support with Fish-Oil Emulsion on Spinal Cord Recovery in Rats with Traumatic Spinal Cord Injury - (:unkn) unknown (TURKISH NEUROSURGICAL SOC, 2011)
AIM: Aim of this study is to assess effects of parenteral nutritional support with fish-oil emulsion on spinal cord recovery in rats with traumatic spinal cord injury. MATERIAL and METHODS: For 5 days after SCI rats were received saline in group C and Omegaven in group O. Locomotor strengths (BBB scale)of animals were rated at Day 0,7,14,21,28, and 35. At Day 35 spinal cord sampling was evaluated immunohistochemically. RESULTS: BBB scores were 0 in early period after SCI was inflicted in both groups. BBB scores were progressively increased after Day 7 in both groups (p <.005). BBB scores were significantly higher in group O when compared with control group after Day7 in all times (p <.005). Neuronal injury (p <.002) and edema was much more in control group when compared with in group O (p <.005). Scores for white mater cavitation, demyelinization and vessel in growth were similar in both groups. VEGF expression in control group was higher (p=.019). CONCLUSION: At the early period of SCI fish-oil emulsion treatment in rats, its anti-inflammatory effects leaded to decrease in edema and had positive effect at the prevention of neuronal injury. We believe that nutritional support with fish-oil emulsion in patients with SCI will result in patient's better clinical outcome and increase in quality of the patient's life.
Keywords: Omega-3 fatty acids; Omega-6 fatty acids; Neuron recovery; Nutrition; Spinal cord injury; ENDOTHELIAL GROWTH-FACTOR; FATTY-ACIDS; EXPRESSION; OMEGA-3-FATTY-ACIDS; INFLAMMATION